Microbiome and metabolome in diagnosis, therapy, and other strategic applications - Faintuch, Joel; Faintuch, Salomao (Academic Press, 2019)
Microbiome and Metabolome in Diagnosis, Therapy, and Other Strategic Applications is the first book to simultaneously cover the microbiome and the metabolome in relevant clinical conditions. In a pioneering fashion, it addresses not only the classic intestinal environment, but also the oral, gastric, lung, skin and vaginal microbiome that is in line with the latest investigations. Nonbacterial microbiomes, such as fungi and viruses are not overlooked, and the plasma microbiome is also discussed. As plasma, brain, placenta, tumor cells, and other sterile fluids and tissues, are increasingly recognized to potentially host a microbiome, albeit a limited one, this is a timely resource. The book's editors were fortunate to have the input of renowned collaborators from nearly all continents. This is truly an international effort that brings the latest in the field to students and professionals alike.